Dual and single career couples in Switzerland: Exploring partners’ trajectories - René Levy; Felix Bühlmann; Eric Widmer (Journal of Family Research, 2007)
Based on retrospective data from a sample of 602 women and 621 men living in couples surveyed in Switzerland in early 1999, professional trajectories of partners are compared using the optimal matching technique in order to distinguish typical sequence models. We identify dual-career couples and distinguish them from other couples with dual- or single-employment, showing that dual-career couples proper are a rather rare phenomenon, and that mobility trajectories continue to be strongly gendered: male trajectories respond to a predominantly occupational logic, whereas female trajectories are structured by both an occupational and a familial logic. A multinomial regression analysis allows to identify some of the factors conditioning couples’ trajectory constellations.